Neck mass in a premature infant. Issue 2 (March 2015) - Tucker, Elizabeth; Peter-Wohl, Sigal; Warner, Diane D.
Abstract: Fibromatosis colli is the most common cause of neck mass in the neonatal period, occurring in 0.4% of live births worldwide. The pathophysiology of fibromatosis colli is unclear. The most accepted causes involve fetal malpositioning, such as breech presentation, and birth trauma with subsequent ischemia of the sternocleidomastoid muscle. We present an infant with fibromatosis colli born at the earliest gestational age and with the lowest birth weight of any case previously documented. His only risk factor for fibromatosis colli was breech presentation, a common condition at his gestational age. This case suggests alternative mechanisms may lead to fibromatosis colli.